2018
DOI: 10.1007/s10606-018-9309-1
|View full text |Cite
|
Sign up to set email alerts
|

Aligning Concerns in Telecare: Three Concepts to Guide the Design of Patient-Centred E-Health

Abstract: The design of patient-centred e-health services embodies an inherent tension between the concerns of clinicians and those of patients. Clinicians' concerns are related to professional issues to do with diagnosing and curing disease in accordance with accepted medical standards. In contrast, patients' concerns typically relate to personal experience and quality of life issues. It is about their identity, their hopes, their fears and their need to maintain a meaningful life. This divergence of concerns presents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 62 publications
0
33
0
1
Order By: Relevance
“…Finally, there is a need to ensure the user is aware of the functionality and quality of content, which should be delivered plainly using the app description page. The future direction of mHealth app development to support caregiving engagement would therefore entail the inclusion of iterative user‐centred design (Tighe et al, 2020), most notably the participatory design principles, to ensure the design of the app includes an iterative process for development with the user at the centre of the design; guiding the process of design and usability based on their needs and requirements (Andersen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there is a need to ensure the user is aware of the functionality and quality of content, which should be delivered plainly using the app description page. The future direction of mHealth app development to support caregiving engagement would therefore entail the inclusion of iterative user‐centred design (Tighe et al, 2020), most notably the participatory design principles, to ensure the design of the app includes an iterative process for development with the user at the centre of the design; guiding the process of design and usability based on their needs and requirements (Andersen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research has shown that discrepancy in patients’ and HCP’s perceptions of which information is important for health care staff to know and respond to may lead to disappointments [ 38 ]. A central aspect in the design of such functionalities is the “alignment of concerns” between patients and HCPs to ensure that the shared information is considered meaningful, actionable, and feasible from the perspectives of both patients and HCPs [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our study does not allow us to draw conclusions about the actual value of the desired eHealth functionalities for co-care, including cost-effectiveness and clinical outcomes. Nevertheless, we believe that the multistakeholder co-design workshops provided an effective forum for the PwP and HCPs to discuss and align their concerns, which has been described as a prerequisite for successful design and implementation [ 39 ]. This may have been confirmed by the high ratings of the importance of all co-designed functionalities in our evaluation questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…These challenges need to be addressed to ensure new technological solutions are acceptable to their target end users. However, to date, researchers do not fully understand the scope and complexity of including users in the design of the care support system (10). This leads to issues in adoption of the solutions proposed.…”
Section: Introductionmentioning
confidence: 99%